2015
DOI: 10.1111/psyp.12455
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation training assisted by heart rate variability biofeedback: Implication for a military predeployment stress inoculation protocol

Abstract: Decreased heart rate variability (HRV) is associated with posttraumatic stress disorder (PTSD) and depression symptoms, but PTSD's effects on the autonomic stress response and the potential influence of HRV biofeedback in stress relaxation training on improving PTSD symptoms are not well understood. The objective of this study was to examine the impact of a predeployment stress inoculation training (PRESTINT) protocol on physiologic measures of HRV in a large sample of the military population randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 48 publications
0
46
0
1
Order By: Relevance
“…The biofeedback data are displayed on the screen of a personal computer (n = 24) or a mobile/portable device (n = 15). The ambient medium allows the users to receive biofeedback information through the surroundings in a physical Larkin et al, 1992;Goodie and Larkin, 2006;McCraty et al, 2009;Strunk et al, 2009;Cutshall et al, 2011;Henriques et al, 2011;Morarend et al, 2011;Edvardsson et al, 2012;Moraveji et al, 2012;Paul and Garg, 2012;Sanchez et al, 2012;Sutarto et al, 2012;Wells et al, 2012;Wu et al, 2012Wu et al, , 2015Prinsloo et al, 2013;Peira et al, 2014;Whited et al, 2014;Lewis et al, 2015;Pusenjak et al, 2015;Sarabia-Cobo, 2015;Meier and Welch, 2016;Munafò et al, 2016Animations Feijs et al, 2013Al Osman et al, 2016 Visual scene Bouchard et al, 2012;De Jonckheere et al, 2014;Gaggioli et al, 2014;Dillon et al, 2016;van Rooij et al, 2016 Virtual character Chittaro and Sioni, 2014;Arroyo-Palacios and Slater, 2016 Modified game Parnandi et al, 2013;Kotozaki et al, 2014 Ambient light Snyder et al, 2015 Auditory Musical expression Yokoyama et al, 2002;Morarend et al, 2011;Vidyarthi and Riecke, 2013;...…”
Section: Interactive Mediamentioning
confidence: 99%
“…The biofeedback data are displayed on the screen of a personal computer (n = 24) or a mobile/portable device (n = 15). The ambient medium allows the users to receive biofeedback information through the surroundings in a physical Larkin et al, 1992;Goodie and Larkin, 2006;McCraty et al, 2009;Strunk et al, 2009;Cutshall et al, 2011;Henriques et al, 2011;Morarend et al, 2011;Edvardsson et al, 2012;Moraveji et al, 2012;Paul and Garg, 2012;Sanchez et al, 2012;Sutarto et al, 2012;Wells et al, 2012;Wu et al, 2012Wu et al, , 2015Prinsloo et al, 2013;Peira et al, 2014;Whited et al, 2014;Lewis et al, 2015;Pusenjak et al, 2015;Sarabia-Cobo, 2015;Meier and Welch, 2016;Munafò et al, 2016Animations Feijs et al, 2013Al Osman et al, 2016 Visual scene Bouchard et al, 2012;De Jonckheere et al, 2014;Gaggioli et al, 2014;Dillon et al, 2016;van Rooij et al, 2016 Virtual character Chittaro and Sioni, 2014;Arroyo-Palacios and Slater, 2016 Modified game Parnandi et al, 2013;Kotozaki et al, 2014 Ambient light Snyder et al, 2015 Auditory Musical expression Yokoyama et al, 2002;Morarend et al, 2011;Vidyarthi and Riecke, 2013;...…”
Section: Interactive Mediamentioning
confidence: 99%
“…Participants across both groups exhibited significant decreases in ANS stress response from pre-training to posttraining with BFT participants experiencing a 25% decrease in ANS stress response compared to the control group who experienced a 16% decrease. This is not in-line with findings associated with longer BFT programs (e.g., [31]) or condensed BFT programs [18] Alternatively, the reduction in stress metrics during the course of the experiment may be due to natural circadian decay across the duration of the study [45].…”
Section: Discussionmentioning
confidence: 35%
“…Another group examined the impact of BFT on military participants during pre-deployment training and found that a 20 minute BFT session resulted in significant decreases in ANS response, as measured by HRV, during assessment in a multimedia combat stress environment. These studies suggest that a condensed BFT may provide adequate training to facilitate participants' successful learning and implementation of the biofeedback technique to reduce subsequent stress response [18].…”
Section: Biofeedback Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Soldiers filled out anonymous 30 minute self-report questionnaires that included several standardized psychological scales, and assessments of coping behaviors, combat exposure, and help-seeking behaviors (see Measures section). Additional details on procedures are available in Lewis et al (2015).…”
Section: Methods Sample and Proceduresmentioning
confidence: 99%